Nanoporous graphene enriched with Fe/Co-N active sites as a promising oxygen reduction electrocatalyst for anion exchange membrane fuel cells - Palaniselvam, Thangavelu; Kashyap, Varchaswal; Bhange, Siddeswar N.; Baek, Jong-Beom; Kurungot, Sreekumar (Advanced Functional Materials, 2016)
Here, a simple but efficient way is demonstrated for the preparation of nanoporous graphene enriched with Fe/Co-nitrogen-doped active sites (Fe/Co-NpGr) as a potential electrocatalyst for the electrochemical oxygen reduction reaction (ORR) applications. Once graphene is converted into porous graphene (pGr) by a controlled oxidative etching process, pGr can be converted into a potential electrocatalyst for ORR by utilizing the created edge sites of pGr for doping nitrogen and subsequently to utilize the doped nitrogens to build Fe/Co coordinated centers (Fe/Co-NpGr). The structural information elucidated using both XPS and TOF-SIMS study indicates the presence of coordination of the M-N (M = Fe and Co)-doped carbon active sites. Creation of this bimetallic coordination assisted by the nitrogen locked at the pore openings is found to be helping the system to substantially reduce the overpotential for ORR. A 30 mV difference in the overpotential () with respect to the standard Pt/C catalyst and high retention in half wave potential after 10 000 cycles in ORR can be attained. A single cell of an anion exchange membrane fuel cell (AEMFC) by using Fe/Co-NpGr as the cathode delivers a maximum power density of approximate to 35 mWcm(-2) compared to 60 mWcm(-2) displayed by the Pt-based system.
Keywords: electrocatalyst; nitrogen doping; oxygen reduction reaction; porous grapheme; quantum dots